Landscape Architecture The Sense of Places, Models and Applications - Almusaed, Amjad (IntechOpen, 2018)
This book is intended as both an introduction to the discipline for students of landscape architecture, architecture, and planning, and a source of continuing interest for more experienced environmental designers. The book offers various materials for landscape architects and other planning professionals. The book is divided into 4 parts and 17 chapters. Part I "Introduction to the Landscape Architecture Theme" is general reading on landscape architecture. Part II "Art's Replica and Landscape Architecture Model" includes three chapters. This part represents a theoretical and sensitive visual interpretation of landscape architecture. Part III "Sustainable Prototypes of a Contemporary Landscape Architecture" includes four chapters, with sustainability as a concept and guiding thought. Part IV "Landscape Architecture Around the World (Study Cases)" includes 9 chapters with many examples from different geographical practical cases.